2019
DOI: 10.1142/s2010326319500084
|View full text |Cite
|
Sign up to set email alerts
|

The generating function for the Bessel point process and a system of coupled Painlevé V equations

Abstract: We study the joint probability generating function for k occupancy numbers on disjoint intervals in the Bessel point process. This generating function can be expressed as a Fredholm determinant. We obtain an expression for it in terms of a system of coupled Painlevé V equations, which are derived from a Lax pair of a Riemann-Hilbert problem. This generalizes a result of Tracy and Widom [24], which corresponds to the case k = 1. We also provide some examples and applications. In particular, several relevant qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…They expressed F α (x 1 , s 1 ) in terms of the solution of a Painlevé V equation. An analogous result was recently obtained in [5] for an arbitrary m ≥ 1, where it is shown that F α ( x, s) can be expressed identically in terms of a solution to a system of m coupled Painlevé V equations.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…They expressed F α (x 1 , s 1 ) in terms of the solution of a Painlevé V equation. An analogous result was recently obtained in [5] for an arbitrary m ≥ 1, where it is shown that F α ( x, s) can be expressed identically in terms of a solution to a system of m coupled Painlevé V equations.…”
Section: Introductionsupporting
confidence: 73%
“…In Section 3, we will take advantage of the fact that normalΦ has constant jumps to simplify the differential identity using a Lax pair. In the same spirit, other RH problems with constant jumps related to the Airy and Bessel processes have also been used in [18, 19] to simplify the analysis. However, we mention that if m=1 our RH problem for Y reduces to the RH problem considered by Bothner et al .…”
Section: Model Rh Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…More precisely, the coupled Painlevé II systems have been related to the generating function for the Airy point process in [15], to the Fredholm determinants of the Painlevé II and the Painlevé XXXIV kernel in [42]. A coupled Painlevé V system has been related to the generating function for the Bessel point process in [12].…”
Section: A Painlevé Type Formula Of the Gap Probabilitymentioning
confidence: 99%